The Role of Shortening in the Sevier Hinterland Within the U.S. Cordilleran Retroarc Thrust System: Insights From the Cretaceous Newark Canyon Formation in Central Nevada. Issue 5 (24th May 2021) - Di Fiori, Russell V.; Long, Sean P.; Fetrow, Anne C.; Snell, Kathryn E.; Bonde, Joshua W.; Vervoort, Jeff D.
Abstract: Documenting the spatio‐temporal progression of deformation within fold‐thrust belts is critical for understanding orogen dynamics. In the North American Cordillera, the geometry, magnitude, and timing of contractional deformation across a broad region of Nevada known as the "Sevier hinterland" has been difficult to characterize due to minimal exposures of syn‐contractional sedimentary rocks and overprinting of Cenozoic extension. To address this, we present geologic mapping and U‐Pb zircon geochronology from three exposures of the Cretaceous Newark Canyon Formation (NCF) in central Nevada. In the Cortez Mountains, NCF deposition between ∼119 and 110 Ma is hypothesized to be related to generation of relief by thrusting/folding to the west. In the Fish Creek Range, NCF deposition between ∼130 and 100 Ma was related to motion on an east‐vergent thrust fault. In the Pancake Range, NCF deposition is bracketed between ∼129 and 66 Ma and post‐dated east‐vergent folding. We incorporate these timing constraints into a compilation of deformation timing in the Sevier hinterland. Late Jurassic (∼165 and 155 Ma) shortening, which is largely post‐dated shortening in the Luning‐Fencemaker thrust belt to the west and pre‐dated initial deformation in the Sevier fold‐thrust belt to the east, is interpreted to represent diffuse, low‐magnitude deformation that accompanied eastward propagation of the basal Cordilleran décollement. Cretaceous (∼130 and 75 Ma) hinterland shortening, which includes deformation associated with NCF deposition, was contemporaneous with shortening in the Sevier fold‐thrust belt. This is interpreted to represent long‐duration strain partitioning between the foreland and hinterland during continued coupling above the basal décollement and the progressive westward underthrusting of thick North American lower‐middle crust. Key Points: Deposition of the 130 and 100 Ma Newark Canyon Formation was related to low‐magnitude shortening in the Sevier hinterland Late Jurassic shortening in the Sevier hinterland coincided with eastward migration of the basal Sevier décollement Between ∼130 and 75 Ma, shortening was partitioned between the Sevier fold‐thrust belt and the Sevier hinterland